Upper body anaerobic power and freestyle swimming performance - Kachaunov, M.; Petrov, L. (Journal of Physical Education and Sport, 2020)
Most of the official swimming events involve a significant use of anaerobic energy systems. Therefore, the evaluation of these systems plays an important role in monitoring in swimming. Various laboratory anaerobic tests have been described in the literature, but one of the most commonly used in swimming is the upper body Wingate anaerobic test (WAnT). Some of the studies conducted so far have observed high correlations between the different indicators of WAnT and swimming speed or swimming achievements, and others have observed a lower or no significant correlations.The partisipants in this study are 52 swimmers from the Bulgarian Youth National Swimming Team - 15 girls at an average age of 15.5 ± 1.46 years and 37 boys at an average age of 15.9 ± 1.29 years. They performed the upper body WAnT with a resistance of 5% of body weight. As a result, the WAnT test parameters correlate significantly with the swimming achievements, with the highest correlation being observed between the average power and 50 m freestyle for both sexes- r = -0.788 (p <0.001) for girls and r = -0.811 (p <0.001) for boys). The observed high correlations allow us to recommend the test for anaerobic power monitoring in swimmers.